Role of Quantitative Apparent Diffusion Coefficient in Predicting Genetic Subtypes of Gliomas - Ranabhat, Kajan; Bishokarma, Suresh; Shrestha, Pratyush; Panth, Rajesh; Ghimire, Ram Kumar (Nepal Journal of Neuroscience, 2020)
Introduction: Magnetic resonance morphologic features are widely used in characterising gliomas for predicting grades and thereby aiding in preoperative management planning. We aim to find out if Magnetic Resonance Imaging (MRI) morphologic characters and quantitative apparent diffusion coefficient (ADC) measurements can predict genetic subtypes of high-grade gliomas. Methods and Materials: Preoperative MRI examinations of histopathologically proven gliomas were retrospectively studied for qualitative tumor characteristics, including location, extent, cortical involvement, margin sharpness, cystic component, mineralization or hemorrhage, and contrast enhancement. Quantitative diffusion metrics were also assessed. Chi-square test, students t-test and multivariate regression analysis were used to evaluate the relationship between MRI features and Isocitrate Dehydrogenase (IDH) mutational status. Results: The final study population included 23 patients (sixteen males and seven females, mean age 40 years ± 14.4, age range 13–66 years). Nine tumors were IDH mutant and fourteen were IDH wild type. IDH wild-type tumors showed patchy to diffuse diffusion restriction and a lower apparent diffusion coefficient (ADC) compared to IDH mutant types. T2/FLAIR high signal and maximum ADC values were associated with IDH mutational status. Contrast enhancement, hemorrhage and necrosis were significantly higher in IDH wild type gliomas. There was no statistical difference in the age, gender, tumor burden, location, site and edema between the IDH-mutant and wild-type tumors. Conclusions: Magnetic resonance morphometric parameters that include T2/FLAIR signal character, contrast enhancement pattern, hemorrhage and necrosis and quantitative mean ADC /normalized ADC can support preoperatively the distinction of genetic subtypes of gliomas.